2003
DOI: 10.1653/0015-4040(2003)086[0154:fasocs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and Survival of Citrus Sharpshooters (Hemiptera: Cicadellidae) on Host Plants

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
(14 reference statements)
0
8
0
7
Order By: Relevance
“…Milanez et al (2001) in Brazil reported similar alternative host selection behavior in two other cicadellids, Dilobopterus costalimai Young and Oncometopia facialis (Signoret), transmitting X. fastidiosa in citrus. In another study, Milanez et al (2003) reported 40 Ð 62% mortality in adult males and females D. costalimai and O. facialis caged on potted sweet orange, Citrus sinensis (L.), for 96 h (no-choice test situation). Sweet orange is a common Þeld host of these cicadellids.…”
Section: Discussionmentioning
confidence: 99%
“…Milanez et al (2001) in Brazil reported similar alternative host selection behavior in two other cicadellids, Dilobopterus costalimai Young and Oncometopia facialis (Signoret), transmitting X. fastidiosa in citrus. In another study, Milanez et al (2003) reported 40 Ð 62% mortality in adult males and females D. costalimai and O. facialis caged on potted sweet orange, Citrus sinensis (L.), for 96 h (no-choice test situation). Sweet orange is a common Þeld host of these cicadellids.…”
Section: Discussionmentioning
confidence: 99%
“…Concluíram, também, que esse grupo de insetos necessita de hospedeiros alternativos para sobreviver no campo. Milanez et al (2003) verificaram que, num período de 24h, fêmeas de D. costalimai e O. facialis, alimentando-se em plantas de falso boldo, excretaram um volume líquido correspondente a 292 e 430 vezes seus volumes corpóreos, respectivamente. A mortalidade de adultos após 96 h foi menor em hospedeiros onde houve maior excreção, indicando uma relação direta entre a taxa de excreção e a adequação nutricional ao hospedeiro.…”
Section: Palavras-chave: Exigências Térmicas Número De Gerações Cigunclassified
“…O local de alimentação na planta (Lopes, 1996), a baixa taxa de ingestão observada em citros em relação a outras plantas hospedeiras (Milanez et al, 2003) e as condições hídricas do solo que influenciam na sobrevivência e alimentação da cigarrinha na planta hospedeira (Pereira et al, 2005), possivelmente, afetam a eficiência com que diferentes espécies de cigarrinhas adquirem ou inoculam X. fastidiosa.…”
Section: Introductionunclassified